Some Measures to Improve Reading Comprehension Ability for First Graders in Vietnam - Trinh Thi Ha (Zien Journals, 2021)
Reading comprehension is an important competency, which plays a decisive role in the learning process for students at all levels. This is also a matter of concern around the world. Our research is aimed at primary school students in general and first grade students in particular in Vietnam with the desire to improve reading comprehension when studying first-grade Vietnamese textbooks compiled according to Chapters. new general education program (General Education Program in Literature, 2018). Proposing a number of measures to influence the content and organization of teaching reading comprehension in order to form and improve reading comprehension ability for first grade students, contributing to improving the quality of reading for students in the first grade. at the beginning of primary school, meeting the goal of educational reform in Vietnam in the new period.
Keywords: Reading comprehension; language ability; primary school students; Vietnamese